In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.